2011
DOI: 10.1007/s00405-011-1599-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cidofovir intralesional treatment in recurrent respiratory papillomatosis

Abstract: To present the results of recurrent respiratory papillomatosis (RRP) treatment with surgical excision and adjuvant anti-viral cidofovir intralesional use and to examine the correlation between the cidofovir effectiveness and the patient previous history of multiple larynx procedures, age, extension of lesion and dose. 32 patients with laryngeal papillomas were treated with cidofovir in our Department between I.2009 and I.2011. The number of previous RRP debulking procedures ranged from 1 to 100. The intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
(41 reference statements)
0
42
0
5
Order By: Relevance
“…12 A recent systematic review that evaluated the benefits of cidofovir in the treatment of laryngeal papillomatosis included 15 randomized studies in adults and only four in children and found no difference between the drug and placebo. 13 Therefore, the benefits of cidofovir remain questionable.…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent systematic review that evaluated the benefits of cidofovir in the treatment of laryngeal papillomatosis included 15 randomized studies in adults and only four in children and found no difference between the drug and placebo. 13 Therefore, the benefits of cidofovir remain questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the RRP could be brought to cessation permanently, with many authors reporting significantly prolonged treatment intervals. However, not all patients respond to treatment [ 2 ], [ 9 ], [ 30 ], [ 36 ], [ 45 ], [ 51 ]. These studies mentioned showed no or only minimal side effects in the intralesional applications, which differed significantly in doses and intervals.…”
Section: Recurrent Respiratory Papillomatosismentioning
confidence: 99%
“…It is an acyclic nucleoside phosphonate and is therefore independent of phosphorylation by viral enzymes. Cidofovir is the most contemporary adjuvant antiviral treatment for RRP and its topical use is widely described [5]. Since 1998 several articles have reported the results of intralesional cidofovir injection in the treatment of papillomatosis [4].…”
Section: Introductionmentioning
confidence: 99%